Sustainable Development of Graphene Electrodes for Supercapacitors through Laser Scribing of Agrowaste Derived Lignin - Katwesigye, Samuel; El-Khouly, Mohamed E.; López-Salas, Nieves; Khalil, Ahmed S.G. (Materials Science Forum)
The growing rise in agricultural activities has resulted in an increase in unutilized waste which is a significant contributor to greenhouse gas emissions. This has led to a need for sustainable methods to add value to such waste. This work focused on the transformation of agricultural waste into usable products through alkaline treatment to obtain lignin and cellulose, and the evaluation of the derived lignin as a viable carbon precursor in energy storage applications. Laser scribing was used as a fast and simple strategy in producing laser-induced graphene (LIG) electrodes. Lignin was isolated from wheat straw using sodium hydroxide treatment. The pulp from the treatment was subjected to bleaching with sodium chlorite followed by acid hydrolysis to extract microcrystalline cellulose. Fourier-transform infrared spectroscopy (FTIR), Transmission electron microscopy, and Xray diffraction were used for characterization of the materials produced. The fabricated supercapacitor could achieve an areal capacitance (C A ) of 5.12 mF/cm 2 (0.02 mA/cm 2 ). This study illustrated the successful valorization of wheat straw residue into microcrystalline cellulose and the use of extracted lignin in producing graphitic carbon electrodes for supercapacitors.